Stress intensity factors for mixed-mode crack growth in imitation models under biaxial loading (Fracture and Structural Integrity, 2020)
In this study a procedure to stress intensity factors calculation for imitation models made of titanium alloy is described. In service fatigue cracks are detected in a disk and blade “dovetail type” attachment. On the base of this attachment dimensions and with taking into account the biaxial loading conditions of rotating compressor disk the two geometries of imitation model of gas turbine engine compressor disk are developed. To accurate verification of biaxial loading conditions, the first imitation model of constant thickness is used. In order to fully reproduce the geometry of the compressor disk and conditions of mixed mode crack growth, the second imitation model with reduced cross section is proposed. The fatigue crack growth experiments of imitation models were carried out at room temperature on a biaxial testing machine. Two different stress ratio values are applied several times to each imitation model in order to fix the experimental crack front positions. The elastic and plastic stress intensity factors used for the representation of the experimental results are computed by using full-size 3D Finite Element analysis of the imitation models with surface quarter elliptical and through-thickness cracks.
Keywords: Titanium alloy; Mixed-mode; Crack growth; Stress intensity factors; Biaxial loading; Imitation modelling